EL TEMPERAMENTO DEL PERRO DE REFUGIO Y SU INFLUENCIA EN EL APRENDIZAJE DE LAS COMANDOS BÁSICAS Y LA TASA DE ADOPCIÓN (Revista Inclusiones, 2022)
This article's objective was to verify the influence of rescued dogs’ temperament onbasic commands learning and adoption rates. Thus, 30 dogs were evaluated.Temperament data was collected employing the focal animal sampling method in threedifferent environments. A 7-item selection of training commands was also applied inboth basic obedience and retrieval tasks to improve dogs’ overall individualperformance over time. The principal component analysis followed by Spearman’scorrelation coefficient was used to analyze dog temperament scores for the adoptionrate and the time dogs took to learn each training command. Lay down was positivelycorrelated with stay (r=0.4, p